IEEE PES ISGT Europe 2013 2013
DOI: 10.1109/isgteurope.2013.6695464
|View full text |Cite
|
Sign up to set email alerts
|

Hardware-in-the-loop testbed based on hybrid real time simulator

Abstract: The introduction of Smart Grid concept contributes to the development of multiple new algorithms and equipment for their control. The best of currently available tools for this is a simulation. Its advanced application is a technology of hardware-in-the-loop (HIL) testing that allows providing fast prototyping and getting ready to use products in a short time. However the growing complexity of new concepts of control systems demands the improvement of HIL performance in order to make it easier and also allow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The given concept is realized as a specialized software and hardware hybrid complex -Hybrid Real-Time Simulator (HRTSim) of EPS [14,15].…”
Section: The Concepts Of Hybrid Simulation Of Epsmentioning
confidence: 99%
“…The given concept is realized as a specialized software and hardware hybrid complex -Hybrid Real-Time Simulator (HRTSim) of EPS [14,15].…”
Section: The Concepts Of Hybrid Simulation Of Epsmentioning
confidence: 99%
“…Models of automatic control and relay protection systems are implemented via a microprocessor units (MPU), containing a central processing unit (CPU) and functionally oriented peripheral processors (PP), as well as Server depending on the required composition of the input signals and the speed of algorithms execution. The given concept is realized as a specialized software and hardware hybrid complex -Hybrid Real-Time Simulator (HRTSim) of EPS [5,6].…”
Section: Principle Of Hybrid Real Time Simulation Approachmentioning
confidence: 99%
“…Due to the impossibility of making field experiments and tests of these devices in real power systems, the main tools for solving these problems are modeling and simulation. The listed tasks form the following specific requirements for simulation systems necessary for their solution: Numerical investigations of heat and mass transfer processes at the ignition of solid [1][2][3][4], liquid [5][6][7][8] condensed substances and polymer materials [9, 10] by local energy source with limited power consumption (metallic and non-metallic particles, wires, cores, concentrate radiation flows and etc.) was held in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…New generation testbeds are designed and implemented using actual power system control equipment interfaced with actual grid and/or simulation software to allow replication of full-scale cyber-physical system performance at a large laboratory scale. Several papers addressed the development of the power system cyber-physical testbeds [5][6][7][8][9][10][11][12][13][14][15][16][17]. In [5][6][7][8][9], concept of end to end testing using the system in-the-loop (SIL) testbed is presented.…”
Section: Introductionmentioning
confidence: 99%
“…In [5][6][7][8][9], concept of end to end testing using the system in-the-loop (SIL) testbed is presented. In [10][11][12][13][14][15], hardware-in-the-loop (HIL) testing platforms for different studies including distributed generation and power electronic interfaces are discussed. Examples of cyber-physical testbeds to study different concerns related to power system cyberattacks can be found in [16,17].…”
Section: Introductionmentioning
confidence: 99%